Fungal Load on Zea mays Seeds and their Biocontrol - M.Chavan2, Anil U. Kulkarni1; Ashok (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Seed borne fungi of maize (Zea mays) were isolated from fifteen varieties on blotter and different agar media. Total eleven, twelve and twenty fungi were isolated from fifteen varieties of maize on blotter paper, Czepek dox Agar (CZA) and Potato Dextrose Agar (PDA) respectively. Seed mycoflora of abnormal seeds was studied. Maximum incidence of fungi was observed on discoloured seeds followed by cracked and shrunken seeds. Attempts were also made to control seed mycoflora by using Trichoderma viride. Trichoderma viride showed maximum inhibition zone against Alternaria alternata, Fusarium oxysporum, Helminthosporium tetramera, Penicillium notatum and Rhizoctonia solani. ——————————————————————————————————– 1Department of Botany, Lal Bahadur Shashtri College Partur, Dist Jalna, India; 2Department of Botany, Dr. Babasaheb Ambedkar Marathwada University, Aurangabad- 431 004. (M.S.) India * Corresponding Author, Email:Â ram_mango@yahoo.com Please Cite This Article As: Anil U. Kulkarni and Ashok M.Chavan. 2010. Fungal Load on Zea mays Seeds and their Biocontrol. J. Exp. Sci. 1(2): 20-25.